Single-atom electrochemiluminescence probe and its preparation method and application

By loading luminescent metal atoms on MXene materials, single-atom electrochemical luminescence probes are prepared, which solves the problem of insufficient luminescence intensity caused by the short lifetime of excited free radicals in the existing technology, and achieves efficient biological detection.

CN116376552BActive Publication Date: 2025-01-24TSINGHUA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310318811.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-29
Publication Date
2025-01-24
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

In the prior art, metal nanoclusters, as electrochemiluminescent probes, have a short life of excitation radicals, resulting in a weak luminescence intensity and unable to achieve sensitive biological detection.

Method used

By loading luminescent metal atoms on the MXene material with M atom vacancies, the luminescent metal atoms occupy the vacancies of the M atoms on the MXene material to avoid aggregation of the luminescent metal atoms, and a single-atom electrochemical luminescence probe is prepared.

Benefits of technology

The electrochemiluminescence intensity is enhanced and sensitive biological detection is achieved, and the good conductivity and large specific surface area of ​​MXene materials are suitable for electrochemiluminescence sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116376552B_ABST
    Figure CN116376552B_ABST
Patent Text Reader

Abstract

The present application provides a single-atom electrochemical luminescent probe and its preparation method and application. The luminescent probe is composed of the chemical formula M' a ‑R z ‑M n+1 ‑xX n T y It means that M is a transition metal element, X is selected from carbon or nitrogen, n is 1 or 2, x>0, M and X form a MXene structure containing an M atom vacancy; M' is one or more luminescent metal elements selected from Pt, Ru, Au, Ag, Rh, Pd, M' occupies the M atom vacancy, 0<a≤x; R is an organic ligand group combined with M', z>0; T is an oxygen-containing or F-containing functional group combined with the surface of the MXene structure, y>0. The single-atom electrochemiluminescent probe is stably loaded with isolated luminescent metal atoms and can be applied to electrochemiluminescent sensors. The excited free radicals on the luminescent probe are not easily self-quenched, the electrochemiluminescence intensity is enhanced, and sensitive biological detection can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of biological nanomaterials, and in particular to a single-atom electrochemiluminescent probe and a preparation method and application thereof. Background Art

[0002] Electrochemiluminescence (ECL), also known as electrochemiluminescence, is a type of chemiluminescence. It is mainly a phenomenon in which ECL luminophores are generated on the electrode surface by applying voltage, and high-energy electron transfer reactions are carried out to generate electronic excited state luminescence signals. Compared with other optical methods such as photoluminescence, bioluminescence and chemiluminescence, ECL has unique advantages. For example, electrochemiluminescence does not require an external light source and has almost no background signal; it has good spatiotemporal controllability and can be used in trace target detection of biomolecules, clinical diagnosis, environmental and food monitoring, etc.

[0003] The application of electrochemiluminescence detection is mainly based on the basic research of various electrochemiluminescence probes. Metal nanoclusters can be used as electrochemiluminescence probes due to their stable optical and electrochemical properties, monodisperse size and high atomic precision. However, the lifetime of their excited free radicals in the annihilation reaction is short, resulting in weak luminescence intensity, which cannot achieve sensitive biological detection.

[0004] Emerging single-atom catalysts with isolated active metal atoms stabilized on supports are considered to be effective catalysts in electrochemical energy conversion systems. Currently, no efficient single-atom electrochemiluminescence probes have been reported in the field of electrochemiluminescence. Summary of the invention

[0005] The present application provides a single-atom electrochemiluminescent probe and a preparation method and application thereof, aiming to provide a single-atom electrochemiluminescent probe stably loaded with isolated active metal atoms.

[0006] In the first aspect, the present application provides a single-atom electrochemical luminescent probe, wherein the luminescent probe is represented by a chemical formula M' a -R z -M n+1-x X n T y express,

[0007] Wherein, M is a transition metal element, X is selected from carbon or nitrogen, n is 1 or 2, x>0, and M and X form a MXene structure containing M atomic vacancies;

[0008] M' is one or more luminescent metal elements selected from Pt, Ru, Au, Ag, Rh, and Pd, and M' occupies the vacancy of the M atom, 0<a≤x;

[0009] R is an organic ligand group that binds to M', z>0;

[0010] T is an oxygen- or F-containing functional group bound to the surface of the MXene structure, and y>0.

[0011] In the present application, by loading luminescent metal atoms on a MXene material with M atom vacancies, the luminescent metal atoms occupy the vacancies of the M atoms on the MXene material, which can effectively avoid the agglomeration of the luminescent metal atoms, thereby obtaining a single-atom electrochemiluminescence probe. The MXene material as a carrier has good conductivity and a large specific surface area, and can be applied to electrochemiluminescence sensors. The excited free radicals on the luminescent probe are not prone to self-quenching, which enhances the electrochemiluminescence intensity and enables sensitive biological detection.

[0012] In some embodiments of the present application, the transition metal is selected from one or more of Sc, Ti, Zr, V, Nb, Cr, Mo, and Hf.

[0013] In some embodiments of the present application, the luminescent probe has a chemical formula of Pt a -R z -Ti 3-x C2T y express,

[0014] Wherein, R is an organic ligand group that binds to Pt, and z>0;

[0015] T is an oxygen- or F-containing functional group bound to the surface of the MXene structure, and y>0.

[0016] In a second aspect, the present application provides a method for preparing a single-atom electrochemiluminescent probe, comprising the following steps:

[0017] S1 provides a MXene material containing M atomic vacancies;

[0018] S2 uses an atomic layer deposition method on the MXene material to embed a luminescent metal precursor into the M atomic vacancy to obtain a single-atom electrochemical luminescence probe as described in any embodiment of the first aspect.

[0019] In some embodiments of the present application, the luminescent metal precursor includes one or more of (trimethyl)methylcyclopentadienyl platinum and bis(ethylcyclopentadienyl)ruthenium.

[0020] In some embodiments of the present application, the S10 specifically includes:

[0021] S11 provides the chemical formula M n+1 AX n MAX phase materials,

[0022] Wherein, M is a transition metal, A is an element of Group IIIA or IVA, and X is carbon and / or nitrogen.

[0023] n is 1 or 2;

[0024] S12 performs etching treatment on the MAX phase material to remove the A element in the MAX phase material and damage the MA bond, so as to obtain a MXene material containing M atomic vacancies.

[0025] In some embodiments of the present application, the S12 specifically includes:

[0026] S121 dissolving LiF in hydrochloric acid to obtain an etching solution;

[0027] S122: immersing the MAX phase material in the etching solution, so that the A element in the MAX phase material is removed and the MA bond is damaged, so as to obtain a MXene material containing M atomic vacancies.

[0028] Wherein, the mass ratio of the MAX phase material to the LiF is 1:1.6-2.4.

[0029] In some embodiments of the present application, step S2 specifically includes:

[0030] S21 placing the MXene material in an atomic layer deposition chamber at a temperature of 100 to 300° C.;

[0031] S22: continuously blowing an inert gas into the atomic layer deposition chamber to perform annealing treatment on the MXene material, so as to remove the functional groups bound to the M atomic vacancies on the MXene material and activate the M atomic vacancies to obtain an activated MXene material;

[0032] S23, using an inert gas as a carrier, blowing a vaporized luminescent metal precursor into the atomic layer deposition chamber, so that the luminescent metal precursor is embedded in the M atomic vacancies on the activated MXene material, so as to obtain a MXens material on which the luminescent metal precursor is deposited;

[0033] S24 continuously blows an oxidizing gas into the atomic layer deposition chamber to remove the luminescent metal precursors and residual organic ligands that are not combined with the M atomic vacancies on the MXene material, so as to obtain a single-atom electrochemical luminescence probe as described in any embodiment of the first aspect.

[0034] In some embodiments of the present application, in S23, blowing the vaporized luminescent metal precursor into the atomic layer deposition chamber using an inert gas as a carrier specifically includes:

[0035] Using an inert gas as a carrier, a vaporized luminescent metal precursor is blown into the atomic layer deposition chamber in a pulse mode,

[0036] Wherein, in the pulse mode, the pulse cycle includes: an air blowing stage, a breath holding stage, and an air extraction stage; the pulse cycle cycle times are 1 to 10 times.

[0037] In a third aspect, the present application provides an electrochemiluminescent sensor, comprising:

[0038] A glassy carbon electrode is loaded with the single-atom electrochemiluminescent probe described in any embodiment of the first aspect or the single-atom electrochemiluminescent probe prepared by the method described in any embodiment of the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0040] Figure 1 Schematic diagram of the process for preparing the single-atom electrochemiluminescent probe Pt SA-Cp-MXene in the examples of this application.

[0041] Figure 2 Ti prepared in this embodiment 3-x C2T y MXene and Pt SA-Cp-Ti 3-x C2T y XRD pattern of Mxene.

[0042] Figure 3 This is a graph showing the ECL intensity-scanning time curves of different concentrations of ALP in the examples of this application;

[0043] Figure 4 Graph showing the relationship between the ECL intensity and ALP concentration at different concentrations of ALP in the examples of the present application.

[0044] The above drawings have shown clear embodiments of the present application, which will be described in more detail later. These drawings and text descriptions are not intended to limit the scope of the present application in any way, but to illustrate the concept of the present application to those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0045] The various embodiments or implementation schemes in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments.

[0046] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the implementation or examples are included in at least one implementation or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more implementations or examples in a suitable manner.

[0047] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0048] In this application, unless otherwise specified, the luminescent metal precursor may refer to the luminescent metal precursor molecule itself, or may refer to a molecule from which some organic ligand groups are detached during the atomic layer deposition process. The structure of the luminescent metal precursor changes with the temperature of the atomic layer deposition.

[0049] At present, no efficient single-atom electrochemiluminescence probe has been reported in the field of electrochemiluminescence. Since single-atom catalysts with isolated active metal atoms stably mounted on a carrier are considered to be effective catalysts in electrochemical energy conversion systems, in order to develop an efficient single-atom electrochemiluminescence probe, it is first necessary to find a carrier that can stably load isolated active metal atoms.

[0050] The two-dimensional nanomaterial MXene is composed of transition metal carbides, nitrides, and carbonitrides. Its structure is a two-dimensional nanolayer with a thickness of several atoms. Currently, MAX phase is mainly used as the main precursor. MXene material is obtained by etching element A. It has a good specific surface area with good conductivity and is a good carrier in the field of electrochemiluminescence sensing.

[0051] Therefore, the inventors have developed a new method to load single-atom luminescent metals on MXene materials to obtain a single-atom electrochemical luminescence probe. The single-atom electrochemical luminescence probe provided by the present application and its preparation method and application are described in detail below.

[0052] In the first aspect, the present application provides a single-atom electrochemical luminescent probe, the luminescent probe is represented by the chemical formula M' a -R z -M n+1-x X n T y express,

[0053] Wherein, M is a transition metal element, X is selected from carbon or nitrogen, n is 1 or 2, x>0, and M and X form a MXene structure containing M atomic vacancies;

[0054] M' is one or more luminescent metal elements selected from Pt, Ru, Au, Ag, Rh, Pd, M' occupies the vacancy of M atom, 0<a≤x;

[0055] R is an organic ligand group that binds to M', z>0;

[0056] T is an oxygen- or F-containing functional group bound to the surface of the MXene structure, and y>0.

[0057] In this application, M in the chemical formula n+1-x X n T y It represents a MXene material containing M atomic vacancies. The material is synthesized using the MAX phase as the main precursor, where M is a transition metal, A is any element of the IIIA or IVA group, and X is carbon or nitrogen. By etching the A element in the MAX phase, a chemical formula of M is obtained. n+1-x X n T y MXene materials have good conductivity and large specific surface area, which can shorten the electron transmission distance, expand the reaction area, accelerate the electrochemiluminescence reaction, and are suitable as carriers of electrochemiluminescence probes.

[0058] Among them, x can be expressed as the concentration of M atom vacancies in the MXene material. During the etching of the A element, some MA bonds are damaged, resulting in some M atoms falling off during the etching process, so that the MXene material contains a certain concentration of M atom vacancies. It is understandable that the concentration of M atom vacancies is difficult to measure directly, so the specific range of x is not easy to determine. x>0 indicates that there are M atom vacancies in the MXene material.

[0059] T represents oxygen-containing or F-containing functional groups bound to the surface of the MXene structure. The specific type of functional groups is related to the etchant. Oxygen-containing or F-containing functional groups can make MXene materials have good hydrophilicity and are more useful in the field of electrochemiluminescent sensors. y represents the content of oxygen-containing or F-containing functional groups on the luminescent probe. It is also understandable that the specific range of y is not easy to determine. y>0 indicates that there are oxygen-containing or F-containing functional groups on the luminescent probe.

[0060] In the chemical formula, M' is a luminescent metal element, i.e., a luminophore as an electrochemiluminescent probe, which can occupy the M atom vacancy on the MXene material. At the same time, since the MXene material has a large specific surface area, it can effectively prevent the aggregation of the luminescent metal, and thus the free radicals are not easily self-quenched, thereby enhancing the electrochemiluminescence intensity. M' can be selected from one or more of Pt, Ru, Au, Ag, Rh, and Pd according to actual conditions.

[0061] In the general chemical formula, a represents the amount of substitution of the luminescent metal element for the M atom vacancies in the MXene material. It is understandable that the substitution amount is not easy to measure, but the substitution amount of the luminescent metal element for the M atom vacancies will not exceed the concentration of the M atom vacancies, that is, 0<a≤x, indicating that the luminescent metal element can completely or partially replace the M atom vacancies in the MXene material.

[0062] In the general chemical formula, R represents the organic ligand group bound to M'. Since it is difficult to obtain single-atom metals from luminescent metal elements due to strong metallic bonds, it is necessary to use luminescent metal precursors to obtain single-atom metals, thereby further occupying the M atom vacancies on the MXene material. Luminescent metal precursors are generally luminescent metal organic compounds in which luminescent metals are bound to organic ligands. During the deposition of luminescent metal precursors on MXene materials, the luminescent metal precursors will break and some organic ligands will fall off. Therefore, some organic ligands are also bound to the luminescent metal elements on the MXene material. It can be understood that the specific type of organic ligand group is related to the luminescent metal precursor and has no effect on the structure of the luminescent probe. z represents the content of the organic ligand group brought by M' on the luminescent probe, which is also difficult to quantify and is related to the process in the preparation process. z>0 indicates that there are organic ligand groups bound to M' on the luminescent probe.

[0063] Therefore, in the present application, by loading luminescent metal atoms on a MXene material with M atom vacancies, the luminescent metal atoms occupy the vacancies of M atoms on the MXene material, which can effectively avoid the agglomeration of the luminescent metal atoms, thereby obtaining a single-atom electrochemiluminescence probe. The MXene material as a carrier has good conductivity and a large specific surface area, and can be applied to electrochemiluminescence sensors. The excited free radicals on the luminescent probe are not prone to self-quenching, which enhances the electrochemiluminescence intensity and enables sensitive biological detection.

[0064] In some embodiments of the present application, the transition metal is selected from one or more of Sc, Ti, Zr, V, Nb, Cr, Mo, and Hf.

[0065] In some of the above embodiments, specific types of transition metals in the MXene structure are specifically listed. The transition metals and the X element together constitute the skeleton of the MXene material. The above types of transition metals all have good electrical conductivity, which can ensure that the luminescent probe also has good electrical conductivity.

[0066] In some embodiments of the present application, the luminescent probe is composed of the chemical formula Pt a -R z -Ti 3-x C2T y express,

[0067] Wherein, R is an organic ligand group that binds to Pt, and z>0;

[0068] T is an oxygen- or F-containing functional group bound to the surface of the MXene structure, and y>0.

[0069] In some of the above embodiments, the elements in the chemical formula of the luminescent probe are further defined, and a MXene structure with Ti vacancies is formed by Ti and C, so that the luminescent probe has good conductivity; Pt, as a luminescent metal element, has high catalytic activity, which can ensure that the luminescent probe has a strong electrochemical luminescence intensity.

[0070] In a second aspect, the present application provides a method for preparing a single-atom electrochemiluminescent probe, comprising the following steps:

[0071] S1 provides a MXene material containing M atomic vacancies;

[0072] S2 uses the atomic layer deposition method on MXene materials to embed the luminescent metal precursor into the M atomic vacancies to obtain single-atom electrochemiluminescence probes.

[0073] In the present application, firstly, a MXene material containing M atomic vacancies needs to be obtained. The source of the MXene material is not limited, and the MXene material can be purchased through commercial channels or made by oneself. Then, the luminescent metal precursor is precisely embedded in the M atomic vacancies on the MXene material by the atomic layer deposition (ALD) method, thereby achieving atomic-level precise synthesis to obtain a single-atom electrochemical luminescence probe as in any embodiment of the first aspect.

[0074] ALD can be used to precisely control the composition, loading amount, size and distribution of nanoparticles, and to perform ultra-low loading on the surface of MXene materials. The deposited species and their growth mode on the carrier surface can be controlled at the atomic level, so that single luminescent metal atoms with organic ligands can be controllably and stably fixed on the M atom vacancies of the MXene material, thereby avoiding the agglomeration of the luminescent metal. The single-atom chemiluminescent probe thus obtained has the beneficial effects of any embodiment of the first aspect.

[0075] In some embodiments of the present application, the luminescent metal precursor includes one of (trimethyl)methylcyclopentadienyl platinum and bis(ethylcyclopentadienyl)ruthenium.

[0076] In some of the above embodiments, a luminescent metal precursor that can be used for atomic layer deposition is specifically listed, which needs to be vaporized under suitable conditions to form isolated luminescent metal single atoms with organic ligands, which is conducive to controllably and stably fixing it on the M atom vacancy of the MXene material. Those skilled in the art can make corresponding choices according to actual needs. As an example, in some embodiments, (trimethyl) methylcyclopentadienyl platinum (MeCpPtMe3) can be used as a luminescent metal precursor.

[0077] In some embodiments of the present application, S10 specifically includes:

[0078] S11 provides the chemical formula M n+1 AX n MAX phase materials,

[0079] Wherein, M is a transition metal, A is an element of Group IIIA or IVA, and X is carbon and / or nitrogen.

[0080] n is 1 or 2;

[0081] S12 performs etching treatment on the MAX phase material to remove the A element in the MAX phase material and damage the MA bond, so as to obtain a MXene material containing M atomic vacancies.

[0082] In some of the above embodiments, a MXene material containing M atom vacancies is obtained by etching a MAX phase material. The homemade MXene material can be obtained by controlling the etching conditions to obtain a MXene material with a suitable M atom vacancy concentration, thereby obtaining a luminescent probe with better electrochemiluminescence performance. As an example, the chemical formula of the MAX phase material is Ti3AlC2.

[0083] In some embodiments of the present application, S12 specifically includes:

[0084] S121 dissolving LiF in hydrochloric acid to obtain an etching solution;

[0085] S122 immerses the MAX phase material in an etching solution to remove the A element in the MAX phase material and damage the MA bond, thereby obtaining a MXene material containing M atomic vacancies.

[0086] Among them, the mass ratio of MAX phase material to LiF is 1:1.6-2.4.

[0087] In some of the above embodiments, the method of etching the MAX phase material is specifically defined, and a hydrochloric acid solution of LiF is used as an etching solution to etch the A element in the MAX phase material, and the MA bond is damaged, thereby obtaining a MXene material containing M atomic vacancies. It can be understood that the greater the mass ratio of the MAX phase material to the LiF in the etching solution, the smaller the M atomic vacancy concentration of the obtained MXene material, and the less the amount of the luminescent metal precursor that can be loaded, which will reduce the electrochemical luminescence performance of the luminescent probe, and may cause incomplete etching of the A element layer; the smaller the mass ratio, the higher the loadable amount of the luminescent metal precursor, but if the vacancy is too high, it will cause the MXene material to be unstable, and the loadable amount of the luminescent metal precursor will be reduced. Therefore, when the mass ratio of the MAX phase material to LiF is controlled within the range of 1:1.6 to 2.4, the M atomic vacancy concentration of the MXene material is high, and the structure is stable, and the obtained luminescent probe has good electrochemical luminescence performance.

[0088] It is understandable that, in addition to limiting the mass ratio of MAX phase material to LiF to obtain suitable M atom vacancies, the present application does not have any special restrictions on other process parameters for preparing MXene materials containing M atom vacancies, and those skilled in the art can prepare them according to known techniques and equipment. As an example, S12 is specifically as follows: 1.2g LiF is dissolved in 10mL 9mol / L hydrochloric acid in a polytetrafluoroethylene container, and then 0.5g Ti3AlC2 powder is added under stirring, and the reaction is carried out at 35°C for 24h to obtain a clay-like Ti 3-x C2T y MXene suspension; the clay-like Ti 3-x C2T y After centrifugation of the MXene suspension, the precipitate was collected and washed with water until the pH value was 6-7. During this process, the Ti-Al bond was damaged and some Ti atoms (in the Ti1 and Ti3 sublayers) were peeled off. The washed precipitate was redispersed to obtain a MXene suspension. The MXene suspension was ultrasonically treated for 2 h under argon flow protection and then centrifuged at 3500 rpm for 1 h to obtain Ti 3-x C2T y The MXene homogenous supernatant can be further dried to obtain a MXene solid material, or the homogenous supernatant can be directly stored at 4°C for later use.

[0089] Since MXene materials are two-dimensional nanomaterials and are not easy to redisperse after drying, using MXene homogeneous supernatant for subsequent atomic layer deposition steps is conducive to obtaining single-atom electrochemiluminescence probes with better performance.

[0090] In some embodiments of the present application, step S2 specifically includes:

[0091] S21 places the MXene material in an atomic layer deposition chamber at a temperature of 100 to 300°C;

[0092] S22: continuously blowing an inert gas into the atomic layer deposition chamber to anneal the MXene material, so as to remove the functional groups bound to the M atom vacancies on the MXene material and activate the M atom vacancies to obtain an activated MXene material;

[0093] S23 uses an inert gas as a carrier to blow a vaporized luminescent metal precursor into the atomic layer deposition chamber, so that the luminescent metal precursor is embedded in the M atomic vacancies on the activated MXene material to obtain a MXens material on which the luminescent metal precursor is deposited;

[0094] S24 continuously blows an oxidizing gas into the atomic layer deposition chamber to remove the luminescent metal precursors and residual organic ligands that are not combined with the M atomic vacancies on the MXene material to obtain a single-atom electrochemical luminescence probe.

[0095] In some of the above embodiments, in S21, the temperature of the atomic layer deposition chamber is limited. When performing atomic layer deposition, the luminescent metal precursor needs to be vaporized so that it is embedded in the M atomic vacancies in the MXene material. In this process, the luminescent metal precursor will break and some organic ligand groups will fall off. It can be understood that the higher the temperature, the easier it is for the organic ligand groups to fall off. The precursor that has fallen off some of the organic ligand groups will expose the active sites of the luminescent metal and weaken the steric hindrance deposited on the surface of the MXene material, which is conducive to the better embedding of the luminescent metal precursor in the M atomic vacancies; however, if the temperature is too high and all the organic ligand groups fall off, it will affect the electrochemical luminescence intensity of the luminescent probe, so it is necessary to control the temperature of the atomic layer deposition chamber within the range of 100 to 300°C. For example, it can be 100°C, 150°C, 200°C, 250°C, 300°C, and the range composed of any of the above values.

[0096] In some embodiments, in S21, the MXene material can be ultrasonically dispersed in anhydrous ethanol, dropped on a quartz glass sheet and dried, and the quartz sheet and the MXene material are placed in an atomic layer deposition chamber. The drying temperature can be 60 to 120° C., for example, the drying temperature can be 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C., and any of the above values.

[0097] In S22, since the M atom vacancies on the surface of the MXene material are unstable, some oxygen-containing or fluorine-containing functional groups will be combined with the M atom vacancies. Therefore, the MXene material needs to be annealed in an inert environment to remove the functional groups occupying the M atom vacancies and activate the M atom vacancies, so that the luminescent metal precursor can more easily occupy the M atom vacancies.

[0098] In some embodiments, in S22 , the annealing treatment time may be 5 to 60 minutes; and the flow rate of the inert gas may be 0.3 to 1 L / min.

[0099] In S23, an inert gas is used as a carrier to introduce the vaporized luminescent metal precursor into the atomic layer deposition chamber, so that the self-limiting surface reaction between the luminescent metal precursor and the MXene material ensures that during the saturated exposure, a luminescent metal precursor molecule is nucleated on a nucleation point associated with an M atom vacancy.

[0100] In some embodiments, in S23, the mass ratio of the luminescent metal precursor to the MXene material is 1:1-3.

[0101] In some embodiments, in S23, the flow rate of the inert gas is 10-200 sccm. For example, the flow rate of the inert gas can be 10 sccm, 20 sccm, 50 sccm, 100 sccm, 150 sccm, 200 sccm, or any range thereof.

[0102] In S24, since there may be an excess of luminescent metal precursors in the atomic layer deposition chamber and some organic ligand groups that are broken and detached from the luminescent metal precursors during the deposition process, an oxidizing gas is continuously blown into the atomic layer deposition chamber to remove the luminescent metal precursors and residual organic ligands that are not bound to the M atom vacancies on the MXene material to obtain a single-atom electrochemiluminescence probe.

[0103] In some embodiments, in S24, the oxidizing gas may be oxygen or ozone.

[0104] In some embodiments, the inert gas may be nitrogen or argon.

[0105] In some embodiments of the present application, in S23, blowing the vaporized luminescent metal precursor into the atomic layer deposition chamber using an inert gas as a carrier specifically includes:

[0106] Using inert gas as a carrier, the vaporized luminescent metal precursor is blown into the atomic layer deposition chamber in a pulsed mode.

[0107] Among them, in the pulse mode, the pulse cycle includes: blowing stage, holding breath stage, and exhausting stage; the number of pulse cycle cycles is 1 to 10 times.

[0108] In some of the above embodiments, in order to ensure that the self-limiting surface reaction between the luminescent metal precursor and the MXene material improves the nucleation efficiency of a luminescent metal precursor molecule at a nucleation point associated with an M atom vacancy during saturated exposure, a pulse mode is further used to urge the vaporized luminescent metal precursor into the atomic layer deposition chamber. In one pulse cycle, the luminescent metal precursor is first blown in during the blowing stage, and then the breath holding stage is entered. During the breath holding stage, the luminescent metal precursor molecule nucleates at a nucleation point associated with an M atom vacancy, and then the air extraction stage is entered to remove the unbound luminescent metal precursor and residual organic ligands, and this is repeated for multiple pulse cycles. The advantage of this is that multiple depositions are conducive to the full occupation of the M atom vacancies by the luminescent metal precursor, thereby improving the electrochemical luminescence intensity of the luminescent probe.

[0109] In some embodiments, the duration of the blowing phase is 0.1 to 3 seconds, the duration of the breath-holding phase is 1 to 30 seconds, and the duration of the exhausting phase is 1 to 100 seconds.

[0110] For example, the time of the blowing stage can be 0.1s, 0.2s, 0.3s, 0.4s, 0.5s, 1s, 1.5s, 2s, 2.5s, 3s, and any range thereof; the time of the breath-holding stage can be 1s, 5s, 8s, 10s, 15s, 20s, 25s, 30s, and any range thereof; the time of the exhausting stage can be 1s, 10s, 20s, 30s, 50s, 70s, 85s, 100s, and any range thereof.

[0111] In a third aspect, the present application provides an electrochemiluminescent sensor, comprising:

[0112] A glassy carbon electrode is loaded with a single-atom electrochemiluminescent probe according to any embodiment of the first aspect or a single-atom electrochemiluminescent probe prepared by a method according to any embodiment of the second aspect.

[0113] In the present application, the single-atom electrochemiluminescent probe according to any embodiment of the first aspect or the single-atom electrochemiluminescent probe prepared by the method according to any embodiment of the second aspect can be loaded on the surface of the glassy carbon electrode and used as a working electrode to obtain an electrochemiluminescent sensor. It can be understood that the electrochemiluminescent sensor has the beneficial effects of the first aspect or the second aspect mentioned above.

[0114] In some embodiments, the single-atom electrochemiluminescent probe according to any embodiment of the first aspect or the single-atom electrochemiluminescent probe prepared according to the method of any embodiment of the second aspect is ultrasonically dispersed in water to obtain a suspension with a concentration of 1 to 5 mg / mL, and 1 to 10 μL of the suspension is dropped onto the surface of a pre-polished glassy carbon electrode, and the glassy carbon electrode is obtained by incubation and drying.

[0115] In some embodiments, the electrochemiluminescent sensor may further include: a test solution, wherein the test solution has a pH of 8 to 10, a NaCl ion concentration of 0.1 to 0.5 mol / L, a substrate disodium phenylphosphate concentration of 1 to 10 mmol / L, and an activator Mg 2+ The concentration is 1-10 mmol / L, and the concentration of the co-reaction reagent tripropylamine is 20-100 mmol / L.

[0116] In some of the above embodiments, the electrochemiluminescent sensor can be used to detect alkaline phosphatase (ALP). Alkaline phosphatase is detected by Mg under the environment of appropriate pH and ion concentration. 2+ After activation, disodium phenylphosphate can be converted into phenol. Then, the glassy carbon electrode is placed in the test solution for ECL detection. Since the stronger the ALP activity in the test solution, the larger the phenol oxidation current, the more obvious the subsequent oxidation current decrease of tripropylamine and single-atom electrochemiluminescence probe. Therefore, the standard curve method can be used to quantitatively analyze ALP according to the strength of the detected electrochemiluminescence signal.

[0117] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0118] Example 1

[0119] The schematic diagram of the preparation process of single-atom electrochemiluminescence probe Pt-SA-Cp-Mxene is as follows Figure 1 shown.

[0120] Ti 3-x C2T y Preparation of MXene: 1.2 g LiF was dissolved in 10 mL 9 mol / L hydrochloric acid in a polytetrafluoroethylene container, and then 0.5 g Ti3AlC2 powder was added under stirring and reacted at 35 °C for 24 h to obtain clay-like Ti 3-x C2T y MXene suspension; the clay-like Ti 3-x C2T y After centrifugation of the MXene suspension, the precipitate was collected and washed with water until the pH value was 6-7; the washed precipitate was redispersed to obtain a MXene suspension, and the MXene suspension was ultrasonically treated for 2 h under the protection of an argon flow, and then centrifuged at 3500 rpm for 1 h to obtain Ti 3-x C2T yMXene homogenized supernatant and directly stored the homogenized supernatant at 4 °C for later use.

[0121] Single-atom electrochemiluminescence probe Pt SA-Cp-Ti 3-x C2T y Preparation of Mxene:

[0122] 2 mg / mL Ti 3-x C2T y 10 mL of the MXene homogenized supernatant was dropped onto a quartz glass sheet, dried, and placed in the deposition chamber of an atomic layer deposition apparatus (Savannah 100, Cambridge Nanotechnology Inc., USA), with the temperature set to 200 °C;

[0123] Continuously blow nitrogen (purity: 99.999%) into the atomic layer deposition chamber to anneal the MXene material. The annealing time is 30 min and the nitrogen flow rate is 0.5 L / min.

[0124] Then, nitrogen gas was used as a carrier to blow gasified MeCpPtMe3 into the atomic layer deposition chamber in a pulse mode. The pulse cycle included: a 1s blowing stage, a 5s holding stage, and a 20s pumping stage. The pulse cycle was repeated 5 times. The nitrogen flow rate was 50sccm, and the total amount of MeCpPtMe3 blown was 10mg.

[0125] Ozone was continuously blown into the atomic layer deposition chamber for 30 min, and the oxygen flow rate was 0.5 L / min to obtain the single-atom electrochemiluminescence probe Pt SA-Cp-Ti 3-x C2T y Mxene.

[0126] The prepared Ti 3-x C2T y MXene and Pt SA-Cp-Ti 3-x C2T y Mxene was subjected to X-ray diffraction (XRD) analysis, and the results were as follows Figure 2 As shown, compared with the X-ray diffraction (XRD) pattern of bulk Ti3AlC2 (curve a), Ti 3-x C2T y The (104) peak of MXenes (curve b) disappeared after stripping, and the peak position of the (002) diffraction peak moved from 9.5° to 6°, and the corresponding basal plane spacing was also enlarged accordingly, indicating the successful etching of MXene. 3-x C2T yThe characteristic crystal planes of Pt (111), (200), and (220) were not observed in the XRD pattern of MXenes (curve c), which indicates that the single atomic layer was precisely controlled during the synthesis process and no long-range ordered crystals with Pt-Pt bonds were formed.

[0127] Example 2

[0128] Preparation of glassy carbon electrode: The single-atom electrochemiluminescence probe Pt SA-Cp-Ti obtained in Example 1 was 3-x C2T y Mxene was ultrasonically dispersed in water to obtain a suspension with a concentration of 3 mg / mL, 10 μL of the suspension was dropped onto the surface of the pre-polished glassy carbon electrode, and the glassy carbon electrode was obtained by incubation and drying;

[0129] Prepare the test solution: dissolve sodium chloride, disodium phenylphosphate, magnesium chloride and tripropylamine in 50mmol / L Tris-HCl buffer (pH=9) to obtain a test solution, wherein the concentration of sodium chloride is 0.1mol / L, the concentration of disodium phenylphosphate is 4mmol / L, the concentration of magnesium chloride is 1mmol / L, and the concentration of tripropylamine is 25mmol / L.

[0130] Use the test solution to dissolve and dilute alkaline phosphatase to obtain test solutions of alkaline phosphatase with concentrations of 0.1 U / L, 0.2 U / L, 1 U / L, 2 U / L, 5 U / L, 10 U / L, 15 U / L, 20 U / L, and 50 U / L, respectively, and incubate at 25°C for 20 min.

[0131] ECL determination: The above-mentioned glassy carbon electrode was immersed in the solution to be tested. In this study, a three-electrode system was used, with the working electrode being a glassy carbon electrode, the reference electrode being Ag / AgCl (saturated KCl), and the counter electrode being a platinum wire. The potential range was 0-1.8 V, and the scanning rate was 0.1 V / s. The intensity of the electrochemiluminescence signal of the solution to be tested was detected.

[0132] The above alkaline phosphatase test solutions with concentrations of 0.1U / L, 0.2U / L, 1U / L, 2U / L, 5U / L, 10U / L, 15U / L, 20U / L, and 50U / L were respectively used as test solutions for ECL determination. The ECL intensity-scanning time curves of different concentrations of ALP are shown in Figure 3 As shown in Figure 2, the relationship between the ECL intensity of different concentrations of ALP and the ALP concentration is shown in Figure 2. Figure 4 shown.

[0133] from Figure 3It can be seen that as the concentration of alkaline phosphatase increases, the ECL intensity becomes weaker, which also shows that Pt exists on the single-atom electrochemiluminescent probe obtained in Example 1, and has a strong electrochemiluminescence intensity. Combined with the XRD spectrum in Example 1, it shows that Pt is embedded in Ti in the form of a single atom. 3-x C2T y On the Ti vacancy of MXene.

[0134] from Figure 4 It can be seen that when the alkaline phosphatase concentration is in the range of 0.2 to 10 U / L, the ECL intensity is linearly related to the alkaline phosphatase, which indicates that the single-atom electrochemiluminescence probe Pt SA-Cp-Ti obtained in Example 1 3-x C2T y Mxene was used to prepare an electrochemiluminescence sensor, which could be used to quantitatively analyze alkaline phosphatase by ECL determination.

[0135] Detection of ALP in serum samples: The serum sample was diluted with the test solution to obtain a 0.1% (V / V) serum solution, to which different amounts of ALP were added to obtain ALP serum solutions with concentrations of 0.2U / L, 1U / L, 5U / L, and 10U / L, respectively.

[0136] The ALP serum solutions with the above concentrations of 0.2U / L, 1U / L, 5U / L, and 10U / L were respectively used as test solutions for ECL determination. The ALP concentration was calculated according to its ECL intensity and the relationship curve between the above ECL intensity and ALP concentration, which was the measured concentration. The recovery rate was calculated by the following formula. The results are shown in Table 1.

[0137] Recovery rate (%) = measured concentration / actual concentration.

[0138] Table 1

[0139] Actual concentration (U / L) Determination concentration (U / L) Recovery rate (%) 0.2 0.23 115 1. 1.02 102 5 4.97 99.4 10 9.97 99.7

[0140] From the results in Table 1, it can be seen that the recovery rate of ALP in the diluted sample is 99.4% to 115% when ALP is in the range of 0.2 to 10 U / L, indicating that the single-atom electrochemiluminescence probe Pt SA-Cp-Ti 3-x C2T y The Mxene-modified glassy carbon electrode can still be used as an electrochemiluminescence sensor under complex reaction conditions with high sensitivity, and has broad application prospects in the field of solid-state biosensors.

[0141] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A single-atom electrochemiluminescence probe, characterized in that: The luminescent probe has the chemical formula M' a -R z -M n+1- x X n T y express, Wherein, M is a transition metal element, the transition metal is selected from one or more of Sc, Ti, Zr, V, Nb, Cr, Mo, and Hf, X is selected from carbon or nitrogen, n is 1 or 2, x>0, and M and X form a MXene structure containing M atomic vacancies; M' is one or more luminescent metal elements selected from Pt, Ru, Au, Ag, Rh, and Pd, and M' occupies the vacancy of the M atom, 0<a≤x; R is an organic ligand group that binds to M', z>0; T is an oxygen- or F-containing functional group bound to the surface of the MXene structure, and y>0.

2. The single-atom electrochemiluminescence probe according to claim 1, characterized in that: The luminescent probe has a chemical formula of Pt a -R z -Ti 3-x C2T y express, Wherein, R is an organic ligand group that binds to Pt, and z>0; T is an oxygen- or F-containing functional group bound to the surface of the MXene structure, and y>0.

3. A method for preparing a single-atom electrochemiluminescence probe, characterized in that: The following steps are involved: S1 provides a MXene material containing M atomic vacancies; S2 uses an atomic layer deposition method on the MXene material to embed a luminescent metal precursor into the M atomic vacancy, comprising: S21 placing the MXene material in an atomic layer deposition chamber at a temperature of 100-300° C.; S22: continuously blowing an inert gas into the atomic layer deposition chamber to perform annealing treatment on the MXene material, so as to remove the functional groups bound to the M atomic vacancies on the MXene material and activate the M atomic vacancies to obtain an activated MXene material; S23, using an inert gas as a carrier, blowing a vaporized luminescent metal precursor into the atomic layer deposition chamber, so that the luminescent metal precursor is embedded in the M atomic vacancies on the activated MXene material, so as to obtain a MXens material on which the luminescent metal precursor is deposited; S24 continuously blows an oxidizing gas into the atomic layer deposition chamber to remove the luminescent metal precursor and residual organic ligand that are not combined with the M atomic vacancies on the MXene material, so as to obtain the single-atom electrochemical luminescence probe as described in any one of claims 1 to 2.

4. The method according to claim 3, characterized in that The luminescent metal precursor includes one or more of (trimethyl)methylcyclopentadienyl platinum and bis(ethylcyclopentadienyl)ruthenium.

5. The method according to claim 3, characterized in that The S1 specifically includes: S11 provides the chemical formula M n+1 AX n MAX phase materials, Wherein, M is a transition metal, A is an element of Group IIIA or IVA, and X is carbon and / or nitrogen. n is 1 or 2; S12 performs etching treatment on the MAX phase material to remove the A element in the MAX phase material and damage the MA bond, so as to obtain a MXene material containing M atomic vacancies.

6. The method according to claim 5, characterized in that The S12 specifically includes: S121 dissolving LiF in hydrochloric acid to obtain an etching solution; S122: immersing the MAX phase material in the etching solution, so that the A element in the MAX phase material is removed and the MA bond is damaged, so as to obtain a MXene material containing M atomic vacancies. Wherein, the mass ratio of the MAX phase material to the LiF is 1:1.6-2.

4.

7. The method according to claim 3, characterized in that In S23, the step of blowing the vaporized luminescent metal precursor into the atomic layer deposition chamber using an inert gas as a carrier specifically includes: Using an inert gas as a carrier, a vaporized luminescent metal precursor is blown into the atomic layer deposition chamber in a pulse mode, Among them, in the pulse mode, the pulse cycle includes: an air blowing stage, a breath holding stage, and an air extraction stage; the pulse cycle cycle times are 1 to 5 times.

8. An electrochemiluminescence sensor, characterized in that: include: A glassy carbon electrode loaded with the single-atom electrochemiluminescent probe according to any one of claims 1 to 2 or the single-atom electrochemiluminescent probe prepared according to the method according to any one of claims 3 to 7.